Some Characterization of Fuzzy Strongly Super Closed Sets in Fuzzy Topological Space - Dr. M. K. Mishra, Dr. R. Deepa (International Journal of Control and Automation, 2020)
In this paper we have introduced some characterization in terms of new class of Fuzzy sets called Fuzzy strongly (gsp)*-super closed sets, properties of this set and develop the relationship between fuzzy topological spaces described as fuzzy Ts(gsp)*-space, fuzzy gTs(gsp)*-space, fuzzy g*Ts(gsp)*- space and fuzzy g**Ts(gsp)*-space some characterization of fuzzy strongly super continuous mappings  described in this paper.